Action‐effect binding is decreased in motor conversion disorder: Implications for sense of agency. Issue 8 (14th March 2013) - Kranick, Sarah M.; Moore, James W.; Yusuf, Nadia; Martinez, Valeria T.; LaFaver, Kathrin; Edwards, Mark J.; Mehta, Arpan R.; Collins, Phoebe; Harrison, Neil A.; Haggard, Patrick; Hallett, Mark; Voon, Valerie
ABSTRACT The abnormal movements seen in motor conversion disorder are affected by distraction and entrainment, similar to voluntary movement. Unlike voluntary movement, however, patients lack a sense of control for the abnormal movements, a failure of "self‐agency." The action‐effect binding paradigm has been used to quantify the sense of self‐agency, because subjective contraction of time between an action and its effect only occurs if the patient feels that they are the agent responsible for the action. We used this paradigm, coupled with emotional stimuli, to investigate the sense of agency with voluntary movements in patients with motor conversion disorder. Twenty patients with motor conversion disorder and 20 age‐matched and sex‐matched healthy volunteers used a rotating clock to judge the time of their own voluntary key presses (action) and a subsequent auditory tone (effect) after they completed conditioning blocks in which high, medium, and low tones were coupled to images of happy, fearful, and neutral faces. The results replicated those produced previously: it was reported that an effect after a voluntary action occurred earlier, and the preceding action occurred later, compared with trials that used only key presses or tones. Patients had reduced overall binding scores relative to healthy volunteers, suggesting a reduced sense of agency. There was no effect of the emotional stimuli (faces) or other interaction effects. Healthy volunteers with subclinical depressive symptoms had higher overall binding scores. We demonstrate that patients with motor conversion disorder have decreased action‐effect binding for normal voluntary movements compared with healthy volunteers, consistent with the greater experience of lack of control. © 2013 Movement Disorder Society